2013
DOI: 10.5812/hepatmon.13598
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and HLA Typing of Autoimmune Hepatitis From Pakistan

Abstract: BackgroundHuman leukocyte antigen (HLA) typing in autoimmune hepatitis (AIH) has been investigated in different populations and ethnic groups, but no such data is available from Pakistan.ObjectivesThe aim of this study was to evaluate the clinical profile of autoimmune hepatitis (AIH), and determine the associated antigens and alleles by performing HLA typing.Patients and MethodsA total of 58 patients, diagnosed and treated as AIH in the last 10 years were reviewed. Diagnosis was based on International AIH Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 56 publications
2
20
0
3
Order By: Relevance
“…HLA DRB1*0405 was a major susceptible locus for AIH‐1 in China and Japan, and the HLA DRB1*0405‐DQB1*0401 haplotype indicates a high risk of AIH in Japan . However, it was HLA B27 and cw4 that had significant associations with AIH‐1 in West India, and HLA DR6 in Pakistan . The HLA DQB1*0201 allele had a close association with susceptibility to AIH‐2 in Caucasians .…”
Section: Exploration Of Susceptible Genesmentioning
confidence: 96%
“…HLA DRB1*0405 was a major susceptible locus for AIH‐1 in China and Japan, and the HLA DRB1*0405‐DQB1*0401 haplotype indicates a high risk of AIH in Japan . However, it was HLA B27 and cw4 that had significant associations with AIH‐1 in West India, and HLA DR6 in Pakistan . The HLA DQB1*0201 allele had a close association with susceptibility to AIH‐2 in Caucasians .…”
Section: Exploration Of Susceptible Genesmentioning
confidence: 96%
“…The etiology of AIH remains unknown but is postulated to be related to an autoimmune process triggered by either genetic predisposition or environmental agents. AIH is strongly associated with human leukocyte antigens (HLA-DR3 and HLA-DR4, HLA-DR6) [11][12][13][14] . Environmental factors are thought to be the triggering factors for the development of AIH in genetically susceptible individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In South Asian countries, type 2 AIH is relatively prevalent (11.2% in India [26] and 17.2% in Pakistan [27] ), resulting in a lower frequency of type 1 AIH than in East Asian countries ( Table 1 ). However, pediatric patients were only surveyed in Japan, India, and Pakistan.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In one study from Pakistan [27] , HLA-A2, HLA-A9, HLA-A10, HLA-A19, HLA-B15, HLA-B40, and HLA-DR6 were reported as potential disease-related genetic characteristics. These authors reported that HLA-DR6 was the most strongly related factor; however, its clinical significance remains unclear and needs to be further evaluated.…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation